2010
DOI: 10.1159/000272435
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Physical Training Programme on Cognitive Function and Walking Efficiency in Elderly Persons with Dementia

Abstract: Objectives: To study the effects of physical stimulation based on walking exercises, equilibrium and endurance on cognitive function and walking efficiency in patients with dementia. Methods: Randomized controlled trial including 31 subjects suffering from dementia (age: 81.8 ± 5.3 years). The intervention group (n = 16) benefited from a 15-week physical activity programme involving three 1-hour sessions per week. The control group (n = 15) did not practice any physical activities. Before and after rehabilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
231
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(246 citation statements)
references
References 43 publications
11
231
1
3
Order By: Relevance
“…Full texts of the remaining 102 studies were read and the inclusion criteria applied: 15 eligible studies of which three were excluded due to low methodological quality. Twelve studies were included in the systematic review: 11 RCTs (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) and one cluster RCTs (25) , of which one RCT had generated three separate publications. Williams C (2015 pers.…”
Section: Resultsmentioning
confidence: 99%
“…Full texts of the remaining 102 studies were read and the inclusion criteria applied: 15 eligible studies of which three were excluded due to low methodological quality. Twelve studies were included in the systematic review: 11 RCTs (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) and one cluster RCTs (25) , of which one RCT had generated three separate publications. Williams C (2015 pers.…”
Section: Resultsmentioning
confidence: 99%
“…Exercises can heighten or maintain balance [52,53], gait (e.g. walking speed [53], walking efficiency [54]), muscle strength [24] (e.g. ankle strengthening [53], physical strength [55]) and can also slow down physical deterioration in older people residing in nursing homes [53].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this shortcoming, it has been consistently reported that exercise is associated with a reduced risk of dementia and the level of reported physical activity correlates with the incidence of dementia across a number of studies (Andel et al, 2008;Buchman et al, 2012;Larson et al, 2006;Ravaglia et al, 2008). Randomised controlled trials, although few in number, also support exercise as a pro-cognitive intervention in individuals diagnosed with dementia (de Andrade et al, 2013;Kemoun et al, 2010;Van de Winckel et al, 2004;Venturelli et al, 2011;Vreugdenhil et al, 2012). Recently, Coelho et al (2014) reported an increase in plasma BDNF levels in AD patients and healthy controls following a single bout of exercise on the treadmill, this result however was not accompanied by any cognitive testing.…”
Section: Exercise In the Clinicmentioning
confidence: 99%